2010
DOI: 10.2174/156652310793797748
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Production Means for the Manufacturing of Lentiviral Vectors

Abstract: Lentiviral vectors become more and more famous for the use as gene vector for gene therapy purposes for the treatment of acquired or inherited diseases. In this review, the present state of the art of the production of lentiviral vectors is presented with particular emphasis on the large scale production of these vectors for preclinical and clinical purposes. In contrast to oncoretroviral vectors which are produced using stable producer cell lines, clinical grade lentiviral vectors are essentially produced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 94 publications
1
51
0
Order By: Relevance
“…However, this method is extremely sensitive to variations in pH, as well as Ca 2 + and phosphate concentrations, which can affect titer and reproducibility between production runs. Transfection reagents such as polyethylenimine (PEI) are being developed for large-scale, serum-free transfection, which should help overcome the challenges associated with transfection using Ca-Phos (Ansorge et al, 2009;Schweizer and Merten, 2010;Segura et al, 2010). An additional challenge hindering the widespread use of LVV is the significant amount of downstream processing required for concentration and purification of the LVV in order to remove contaminating DNA and other impurities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this method is extremely sensitive to variations in pH, as well as Ca 2 + and phosphate concentrations, which can affect titer and reproducibility between production runs. Transfection reagents such as polyethylenimine (PEI) are being developed for large-scale, serum-free transfection, which should help overcome the challenges associated with transfection using Ca-Phos (Ansorge et al, 2009;Schweizer and Merten, 2010;Segura et al, 2010). An additional challenge hindering the widespread use of LVV is the significant amount of downstream processing required for concentration and purification of the LVV in order to remove contaminating DNA and other impurities.…”
Section: Discussionmentioning
confidence: 99%
“…4A). Column chromatography is also routinely being used for vector purification as it allows for clean separation of LVV from other impurities (Schweizer and Merten, 2010;Segura et al, 2010). To simplify the manufacture of LVV for ex vivo ACT protocols, we performed large-scale transient transfection of 293T cells followed by Benzonase treatment (50 U/ml) and clarification by modified step filtration (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Most of non-HIV derived lentiviral vectors have been reported to be tat and sometimes rev independent, thus falling in the 3 rd or 4 th generation of packaging systems. For clinical trials purposes, both second and third generation lentiviral vector systems were reported although only HIV-1 and EAIV derived vectors have been used (Schweizer and Merten 2010). Contrarily to simple retroviral vectors, the cytotoxicity of some of the lentiviral proteins has hampered the establishment of stable cell lines constitutively expressing vector components.…”
Section: Lentiviral Vectorsmentioning
confidence: 99%
“…Except for the systems reported by and Ni et al (2005), all the packaging cell lines for lentiviral vector production have been based on human 293 cells transformed with oncogenes such as the SV40 (simian vacuolating virus 40) large T antigen -293T -or the Nuclear Antigen of Epstein-Barr Virus -293EBNA. For clinical application human 293 and 293T cells have been the exclusive cell substrates (Schweizer and Merten 2010). However, safety concerns arise from the fact that 90% of noncoding mobile sequences of the human genome are endogenous retrovirus and although most of them are defective, because of mutations accumulation, some are still active (Zwolinska 2006).…”
Section: Lentiviral Vectorsmentioning
confidence: 99%
See 1 more Smart Citation